7x-28+3x-18=6x-12

Simple and best practice solution for 7x-28+3x-18=6x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-28+3x-18=6x-12 equation:


Simplifying
7x + -28 + 3x + -18 = 6x + -12

Reorder the terms:
-28 + -18 + 7x + 3x = 6x + -12

Combine like terms: -28 + -18 = -46
-46 + 7x + 3x = 6x + -12

Combine like terms: 7x + 3x = 10x
-46 + 10x = 6x + -12

Reorder the terms:
-46 + 10x = -12 + 6x

Solving
-46 + 10x = -12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-46 + 10x + -6x = -12 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-46 + 4x = -12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-46 + 4x = -12 + 0
-46 + 4x = -12

Add '46' to each side of the equation.
-46 + 46 + 4x = -12 + 46

Combine like terms: -46 + 46 = 0
0 + 4x = -12 + 46
4x = -12 + 46

Combine like terms: -12 + 46 = 34
4x = 34

Divide each side by '4'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| 14a=6b-b-12a+a | | 4w+2x-y+2w-3x-8y= | | 2w=-9 | | 0.2g=0.7-g | | 80-x+16=65 | | x-3=-14+3 | | -21-5=-40 | | -9n+9=27 | | 4a+5b=7 | | 4xx-8=-12 | | 5x-3y+9w-6y-3w+6x= | | w+2.5= | | 12x-2=10x+10 | | 4x-10=3x+38 | | 2w-1.5= | | 5x-11=136 | | 3w+2y+8x+3x-11y+3w= | | 8x+2=6x+20 | | x(x-x)(x-x)-x*x=110 | | 1.4x+1.2x-3.8=9 | | -.5x+0y=14 | | 3(x+(180-x))-70=200 | | C=kpv+v | | 6x-14=21+x | | -4(5y-5)+2(3y+9)= | | 2(1-10n)=-2(10n-9) | | x(x-x)2-x*x=110 | | (3x+5)(x-1)=0 | | y=2x(3x) | | m+109+26=180 | | 5d-8=-28 | | (2X+85)= |

Equations solver categories